Identity - Orientation - Interface. The adaptive re-use of the NZASM Building in Pretoria, South Africa. Working towards an architecture which aids the orientation of the user and serves to further define the identity of the city - Clarke, Nicholas J. (University of Pretoria, 2013)
Dissertation (MArch(Prof))--University of Pretoria, 2010.